2014
DOI: 10.1186/1880-5981-66-59
|View full text |Cite
|
Sign up to set email alerts
|

Pore pressure distribution in the focal region of the 2008 M7.2 Iwate-Miyagi Nairiku earthquake

Abstract: The pore fluid pressure distribution in the focal region of the 2008 Iwate-Miyagi Nairiku earthquake was investigated through an analysis of the diversity of focal mechanisms. We inverted stress orientations and focal mechanisms directly from P-wave polarity data obtained from a dense aftershock observation network and other temporarily and routinely operated stations. The estimated stress orientation is consistent with that typical of NE Japan. Specifically, the σ1 axis is oriented WNW-ESE nearly parallel to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 20 publications
1
11
0
Order By: Relevance
“…The fluid pools as forms of velocity and electromagnetic conductivity anomalies are found in the root zones of plate boundaries (e.g., the San Andreas fault system; Becken et al, 2008Becken et al, , 2011Kirby et al, 2014), in the middle crust beneath active faults (Hobbs et al, 2004;Matsubara et al, 2004) and beneath volcanic fields (Parsons et al, 1992;Hasegawa and Yamamoto, 1994;Kanda and Ogawa, 2014). The observations support the positive involvement of crustal fluid not only in the clustering earthquakes in active geothermal fields (Todesco et al, 2004;Giammanco et al, 2008) but also in some of the subduction-unrelated inland earthquakes (Spicak and Horalek, 2001;Hainzl, 2004;Okada et al, 2012;Yoshida et al, 2014). Despite the overall acceptance of the influence of deep seated mid-crustal fluid on triggering earthquakes, the actual form of the fluid is not well understood because, by definition, it rarely breaches the earth's surface.…”
Section: Introductionsupporting
confidence: 53%
“…The fluid pools as forms of velocity and electromagnetic conductivity anomalies are found in the root zones of plate boundaries (e.g., the San Andreas fault system; Becken et al, 2008Becken et al, , 2011Kirby et al, 2014), in the middle crust beneath active faults (Hobbs et al, 2004;Matsubara et al, 2004) and beneath volcanic fields (Parsons et al, 1992;Hasegawa and Yamamoto, 1994;Kanda and Ogawa, 2014). The observations support the positive involvement of crustal fluid not only in the clustering earthquakes in active geothermal fields (Todesco et al, 2004;Giammanco et al, 2008) but also in some of the subduction-unrelated inland earthquakes (Spicak and Horalek, 2001;Hainzl, 2004;Okada et al, 2012;Yoshida et al, 2014). Despite the overall acceptance of the influence of deep seated mid-crustal fluid on triggering earthquakes, the actual form of the fluid is not well understood because, by definition, it rarely breaches the earth's surface.…”
Section: Introductionsupporting
confidence: 53%
“…4a), may be one of the manifestations of high stress concentration in the brittle upper crust. While it is considered that reduction in the effective normal stress on a fault as a result of the supply of overpressurized fluids plays key roles in facilitating crustal earthquakes (e.g., Sibson 1992;Hasegawa et al 2005;Yoshida et al 2014), our observations add growing body of evidence that anelastic deformation in the lower crust is equally important in seismogenesis in the upper crust. (Nakajima and Hasegawa 2007) at a depth of 25 km for each grid node located beneath the NKTZ (purple shading in Fig.…”
Section: Discussionmentioning
confidence: 72%
“…On the basis of the observed reactivation of poorly oriented reverse faults, Sibson [, ] suggested that overpressurization of aqueous fluids to near‐lithostatic values is widespread in the lower part of the seismogenic zone. Yoshida et al [] also suggested the presence of high pore fluid pressures along many of the seismogenic faults in the source region of the 2008 Iwate‐Miyagi inland earthquake.…”
Section: Introductionmentioning
confidence: 99%